From Religious Identity to Cultural Citizenship: Identity Transformation and Civil Rights Negotiation among MLKI Banyumas - Abdul Qodir Abdillah; Roibin; Lutfi Mustofa (Faculty of Ushuluddin Syarif Hidayatullah State Islamic University, Jakarta, 2026)
This research examines how the community of religious adherents who are members of the Supreme Council of Belief in the One Almighty God of Indonesia (MLKI) in Banyumas transforms their religious identity into a cultural identity as a strategy to negotiate recognition and obtain civil rights. This article puts forward a conceptual argument that differs from existing legal-administrative studies: rather than viewing recognition solely as a matter of state regulation, this article frames identity transformation as a deliberate practice of cultural citizenship (cultural citizenship). The analysis is built primarily on Amartya Sen's theory of identity specifically the distinction between singular identity, plural identity, and the